Efficacy and safety of a booster dose of the meningococcal A, C, W, Y-tetanus toxoid conjugate vaccine administered 10 years after primary vaccination and long-term persistence of tetanus toxoid conjugate or polysaccharide vaccine. Issue 6 (2nd June 2020) - Quiambao, Beatriz; Peyrani, Paula; Li, Ping; Cutler, Mark W.; Van Der Wielen, Marie; Perez, John L.; Webber, Chris
ABSTRACT: A previous phase 3, randomized, multicenter study showed the immunogenicity of a primary vaccination of subjects aged 11 to 17 years with the quadrivalent meningococcal vaccine conjugated to tetanus toxoid (MenACWY-TT) or the quadrivalent meningococcal polysaccharide vaccine (MenACWY-PS). This extension study evaluated the safety and immunogenicity of a MenACWY-TT booster 10 years after receiving a primary dose of either MenACWY-TT or MenACWY-PS. The primary immunogenicity endpoint was booster response, evaluated using serum bactericidal antibody assays with rabbit complement (rSBA), 1 month postbooster. Safety endpoints included the percentage of subjects experiencing local and general adverse events (AEs) ≤4 days after MenACWY-TT booster. Of 229 subjects enrolled, 169 and 58 in the MenACWY-TT and MenACWY-PS groups, respectively, completed the booster phase. The 1 month postbooster response for each serogroup ranged from 81.5% to 95.7% for MenACWY-TT and 66.7% to 94.1% for MenACWY-PS. Similar percentages of MenACWY-TT and MenACWY-PS recipients had a booster response to serogroups A, W, and Y, whereas more MenACWY-TT recipients than MenACWY-PS recipients had a booster response to serogroup C. For the MenACWY-TT and MenACWY-PS groups, respectively, the MenACWY-TT booster elicited rSBA titers ≥1:8 in 100% and ≥98.0% of subjects across all serogroups; 100% and ≥96.1% of all subjects had titers ≥1:128. No new safety signals were observed during the booster phase. In conclusion, a MenACWY-TT booster dose after receiving either a primary dose of MenACWY-TT or MenACWY-PS elicited robust immune responses and was well tolerated. Functional antibody responses last up to 10 years after primary MenACWY-TT vaccination.